Analysis of the Work Environment, Work Load, Employee Discipline, and Job Satisfaction During the Covid-19 Pandemic In Bangsal District, Mojokerto Regency - Herry Purwanto; Dyah Sawitri; Moch. Saleh (Jurnal Manajemen Sains dan Organisasi, 2023)
Objectives – The purpose of this study was to analyze the direct effect of work environment and workload on job satisfaction and work discipline and the indirect effect of work environment and workload on work discipline through job satisfaction.Design/Methodology/Approach – The research respondents were 35 employees of the Ward District Office of Mojokerto Regency. This study used a research instrument in the form of a questionnaire with the SEM-PLS test and processed using the WARP PLS 8 program.Findings - The results showed that there was a direct effect of the work environment and workload on job satisfaction and work discipline. Job satisfaction has a direct effect on work discipline. The work environment is not proven to have a significant effect on work discipline through job satisfaction and workload is proven to have a significant effect on work discipline through job satisfaction.